Studi Kasus: Pengaruh Kompres Jahe terhadap Penurunan Intensitas Nyeri Punggung Bawah pada Ibu Hamil Trimester III - Puspayani, Nadya Elma; Kartikasari, Aprilia; Purnamasari, Meivita Dewi (Journal of Bionursing, 2025)
Background. Lower back pain in pregnant women is one of the most-commonly-reported complaints with the prevalence varying from 50% to 80% of pregnant women. However, about 80% of pregnant women who experience low back pain do not make any effort to overcome the symptoms. This case study aims to determine the effect of ginger compress on the intensity of low back pain in third-trimester pregnant women. Methods. Implementation of Evidence-Based Nursing (EBN) refers to PICO with a search for articles from 2019-2023 using Google Scholar. 149 articles were collected with the result that ginger compress is an intervention that can be performed to overcome the problem. The compress was impelemented on 2 patients as an intervention group for 20 minutes for three consecutive days with a comparison of 1 patient as a control group. The evaluation was completed by measuring pain intensity every day for three days before and after the intervention. Results. There was a decrease in pain intensity from 6/10 to 1/10 and 6/10 to 1/10 in both patients in the intervention group after the intervention for three days, while in the control group, the pain intensity was 5/10 to 5/10 on day three. Conclusion. There is a decrease in pain intensity after the ginger compress intervention.